The Effect of Score and Profitability on Company Value: An Empirical Study on Companies Listed In The Kompas100 Index in 2020-2022 - Tasya Yusna Ananda; Wendy (ProBisnis : Jurnal Manajemen, 2025)
This study aims to examine the influence of ESG (Environment, Social, and Governance) Score and profitability on company value in companies listed in the Kompas100 index during the 2020-2022 period. The variables used in this study are the disclosure of ESG and profitability (ROA) as independent variables. The research population includes all companies listed in the Kompas100 index in 2020-2022. The sampling technique used the purposive sampling method and produced 156 samples. The data analysis method used was panel data regression analysis with the selection of the best model with the E-Views 13.0 Enterprise application. The results of this study show that ESG Score disclosure has a significant positive influence on company value. Profitability has a negative influence on the value of the company. In addition, the control variables of firm size and firm growth have a positive influence on the company's value, while firm age has a negative influence on the company's value.